The Comparison between Spinal Anesthesia Bupivacaine and Sevoflurane Anesthesia for Cesarean Section on Apgar Score - Bisri, Tatang; Noer Rochmah, Elly; Kurniawan, Arief; Stella, Angela (ACTA Medical Health Sciences, 2023)
The use of the anesthetic technique for cesarean section is still debatable because of the side effects caused by anesthesia for mothers and neonates. The succeed to determine anesthetic technique can be seen from the outcome of the final condition of the mother and the neonates. The assessment of the succeed to determine anesthetic technique in neonates has been using the Apgar score by assessing the clinical status of the newborn in the first and fifth minutes. This research is aimed to understand the comparison between Apgar scores in cesarean section using general anesthesia sevoflurane and spinal anesthesia bupivacaine. This research is analytical retrospective with a cross-sectional study approach, using a total sample of 40 patients who performed cesarean section from August to November 2021, the samples were taken by consecutive sampling. The data was taken from the medical records of the Melinda Mother and Child Hospital, Bandung. The results of this research showed that there was no significant difference in the APGAR Score first minute between general anesthesia and spinal anesthesia (p=0,054) in the fifth minute (p=0,708). There was no effect on APGAR scores in the general anesthesia sevoflurane group and spinal anesthesia bupivacaine group, and both anesthetic groups had a good effect on neonates DOI : 10.35990/amhs.v1n3.p128-136 REFERENCES Prawirohardjo S. Ilmu Bedah Kebidanan. In: Wiknjosastro, Hanifa, editors. Edisi 1. Jakarta: Yayasan Bina Pustaka Sarwono Prawirohardjo; 2007. p. 133. Badan Penelitian dan Pengembangan Kesehatan Kementerian Kesehatan RI. Hasil Rikesdas 2013. Jakarta: Kementerian Kesehatan RI; 2013. p. 174. BKKBN, BPS, Kementerian Kesehatan RI. Survei Demografi dan Kesehatan Indonesia 2017 Provinsi DKI Jakarta. 2012. Available from: http://demografi.bps.go.id/phpfiletree/sdki/BahanAjarSDKI2007/Lainnya/PublikasiSDKI02-03/RingkasanSDKI02-03.pdf Butterworth JF, Mackey DC, Wasnick JD. Morgan & Mikhail’s Clinical Anesthesiology. 5th ed. New York: McGraw-Hill Education; 2013. Tawfik MM, Tolba MA. Chestnut’s Obstetric Anesthesia: Principles and Practice. Anesth Analg. 2019;129(5):e170. Tsen LC, Bateman BT. Anesthesia for Cesarean Delivery. In: Chestnut DH, Wong C, editors. Chestnut’s Obstetric Anesthesia: Principles and Practice. 6th ed. Philadelphia: Elsevier; 2020. Datta S, Kodali BS, Segal S. Obstetric Anesthesia Handbook. 5th ed. New York: Springer; 2010. Katzung BG, Masters SB, Trevor AJ. Farmakologi Dasar dan Klinik. 12th ed. New York: McGraw-Hill Companies, Inc; 2010. Prawirohardjo S. Ilmu Kebidanan Sarwono. 4th ed. Jakarta: PT Bina Pustaka Sarwono Prawirohardjo; 2010. p. 678–81. Wilson DDMJ. Spinal anaesthesia for caesarean section. J Soc Obs Gynaecol Can. 1998;20(8). Neal JM, Rathmell JP. Complications in Regional Anesthesia and Pain Management. 2nd ed. Philadelphia: Lippincott Williams & Wilkins, a Wolters Kluwer business; 2007. Chumpathong S, Chinachoti T, Visalyaputra S, Himmunngan T. Incidence and risk factors of hypotension during spinal anesthesia for cesarean section at Siriraj Hospital. J Med Assoc Thail. 2006;89(8):1127–32. Hadzic A. Hadzic’s Textbook of Regional Anesthesia and Acute Pain Management. 2nd ed. New York: McGraw-Hill Education; 2017. Watterberg KL, Aucott S, Benitz WE, et al. The Apgar Score. Pediatrics. 2015;136(4):819–22. Thavarajah H, Flatley C, Kumar S. The relationship between the five-minute Apgar score, mode of birth, and neonatal outcomes. J Matern Fetal Neonatal Med. 2018;31(10):1335–41. Rumahorbo FT. Perbandingan Nilai Apgar Neonatus pada Seksio Sesar antara Anestesia Umum dan Anestesia Spinal. e-CliniC. 2014;2(2). Christiana M, Bisri T. Perbandingan antara Anestesi Umum dengan Anestesi Spinal untuk Seksio Sesarea terhadap Skor Apgar. Anesthesia dan Critical Care. 2015;(10):99–106. Septivani A, Tanuwidjaja S, Santosa D. Perbandingan skor Apgar bayi yang lahir melalui seksio sesarea terhadap penggunaan anestesi umum dan anestesi lokal di RSUD Al-Ihsan. Prosiding Pendidikan Dokter Universitas Islam Bandung. 2018;519:673–82. Flora L, Redjeki IS, Wargahadibrata AH. Perbandingan efek anestesi spinal dengan anestesi umum terhadap kejadian hipotensi dan nilai Apgar bayi pada seksio sesarea. J Anestesi Perioper. 2014;2(2):105–16. Karaman S, Akercan F, Aldemir O, et al. The maternal and neonatal effects of the volatile anaesthetic agents desflurane and sevoflurane in caesarean section: a prospective, randomized clinical study. J Int Med Res. 2006;34.